Endolymphatic Sac Tumor in Two Dogs. (July 2017) - Barnes, K. J.; Clear, V.; Youmans, K.; Hardcastle, M. R.; Nelson, N.; Petersen, A.; Kiupel, M.
Endolymphatic sac tumors (ELSTs) are rare neoplasms of the inner and middle ear described in humans. Diagnosis of such neoplasms is difficult and largely dependent on a combination of histologic, immunohistochemical, and clinical findings. Although the neoplastic cells lack cellular features of malignancy, these are clinically aggressive tumors that often invade the surrounding temporal bone. Here, we describe 2 dogs with middle ear masses that share morphologic, immunohistochemical, and clinical similarities with human ELSTs. Advanced imaging of the masses revealed evidence of aggressive behavior such as bony lysis of the temporal bone. Histologically, the neoplastic epithelial cells formed papillary structures, lacked mitotic figures, and had mild anisocytosis and anisokaryosis. The neoplastic cells were immunohistochemically positive for cytokeratin AE1/AE3 but were negative for chromogranin, synaptophysin, and thyroglobulin. Local invasion and bone destruction but no evidence of metastases suggest a clinical behavior similar to human ELSTs.